THE INFLUENCE OF WORK MOTIVATION, WORK DISCIPLINE, AND WORK ENVIRONMENT ON PRODUCTIVITY HEALTH PERSONNEL WORK AT UPTD MUARA BATU HEALTH CENTER - Dea Fitria; Azhar; Faisal Matriadi; Khairawati (RADJA PUBLIKA, 2024)
This research aims to find out the influence of work motivation, work discipline and work environment on the work productivity of health workers at the Muara Batu Health Center UPTD. The aim of this research is to determine the level of work “productivity of Civil Servants (PNS) who work at the UPTD Puskesmas Muara Batu. The data used in this research is primary data obtained by distributing questionnaires to 111 employees. The technique consists of data instrument testing, classical assumption testing and hypothesis testing using the SPSS software program. The results of the research show that work motivation has a positive and significant effect on work productivity at the Muara Batu Health Center UPTD, work discipline has a positive and significant effect on work productivity at the Muara Batu Health Center UPTD, and the work environment has a positive and significant effect on work productivity at the Muara Batu Health Center UPTD. These findings provide useful information for the government to determine strategies related to human resources to increase employee work productivity.